Eosinophils in Cancer: Favourable or Unfavourable? - Sakkal, Samy; Miller, Sarah; Apostolopoulos, Vasso; Nurgali, Kulmira (Current Medicinal Chemistry, 2016)
Eosinophils are granulocytic leukocytes residing in blood and tissues in the lung, breast, gastrointestinal and reproductive systems. Eosinophilia is uncommon in healthy individuals, however, it is associated with allergies, helminth infections and some inflammatory states. Eosinophilia has also been observed in cancer, including colorectal, breast, ovarian, cervical, oral squamous, Hodgkin’s lymphoma and prostate cancer. Whether an increase in eosinophils leading to a favourable or unfavourable prognosis still remains controversial and depends on many factors including the type of cancer. Eosinophil infiltration is considered unfavourable in Hodgkin’s lymphoma, conversely it has also been linked to a favourable prognosis in colorectal, breast and prostate cancers. Eosinophils secrete a variety of cytokines and factors including eosinophil cationic protein, eosinophil-derived neurotoxin, peroxidase and major basic protein which have either anti-tumor effects or stimulate tumor progression. Herein, we discuss the role of eosinophils in tumor immunity and propose mechanisms accounting for their functional differences in tumorigenesis.
Keywords: cancer prognosis